Analysis of the training of canoeists over the four-year Olympic cycle - Baleiunas, E.; Rudzinskas, M.; Skernevicius, J.; Dvedas, E. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2002)
The aim of our work was to investigate the preparation of canoeists - members of the Lithuanian national Olympic team for the Athens Olympic Games throughout a four-year Olympic cycle. The object of the study was the workload distribution over a four-year Olympic preparatory cycle in canoeists, as well as the dynamics of their physical development, physical abilities and functional capacity. We studied three canoeists who participated in the Athens Olympic Games.